The Development And Design Of Rear Upright For The Garuda UNY UG-23 Urban Car - Muhammad Tafif Fadhlurrahman; Febrianto Amri Ristadi (Program Studi Sarjana Terapan Teknik Mesin, Fakultas Vokasi, Universitas Negeri Yogyakarta, 2026)
The development and design of the rear upright for the Urban Car Garuda UNY UG-23 was carried out to improve the previous design that was no longer compatible due to changes in the car frame. This study aimed to find strong and lightweight materials for the rear upright, and to analyze the structure to get the best design with better performance and lower weight. The development method used an engineering approach based on Computer Aided Engineering (CAE). The design process started by using software for parametric, solid modelling, and numerical analysis with the Finite Element Analysis (FEA) method. FEA was used to measure stress, deformation, and safety factors of the rear upright. The simulation also considered different forces, such as the weight on the upright and the force from the brake calliper. The Ashby Method was used to choose materials based on their properties and the design needs. The analysis results showed that the rear upright made from 7075-T6 aluminum met the strength and efficiency requirements. The analysis showed that the factor of safety was at least 15.62 with a maximum stress of 32.34 MPa. The maximum displacement was 0.08 mm and strain was 0.0 mm. The optimization process reduced the mass from 553.64 grams to 322.73 grams. In the best condition (wheel system), the weight was reduced by 41.7% or about 231.64 grams without significantly reducing the strength.